Pengaruh Akuntansi Lingkungan Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Moderasi - Yani Yani; Anny Widiasmara; Abd Rohman Taufiq (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
This study aims to determine the effect of environmental accounting and capital structure on firm value with financial performance as a moderating variable. The sample in this study were 12 BUMN companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The research method used is quantitative research with secondary data collection techniques. The analysis technique uses multiple linear regression analysis and Moderated Regression Analysis (MRA). The analytical tool used is SPSS 21. The results show that environmental accounting has no effect on firm value, capital structure has an effect on firm value. Financial performance is not able to moderate environmental accounting and capital structure on firm valu